Developments in 177Lu-based radiopharmaceutical therapy and dosimetry - George, Siju C.; Samuel, E. James Jebaseelan (Frontiers in Chemistry, 2023)
177Lu is a radioisotope that has become increasingly popular as a therapeutic agent for treating various conditions, including neuroendocrine tumors and metastatic prostate cancer. 177Lu-tagged radioligands are molecules precisely designed to target and bind to specific receptors or proteins characteristic of targeted cancer. This review paper will present an overview of the available 177Lu-labelled radioligands currently used to treat patients. Based on recurring, active, and completed clinical trials and other available literature, we evaluate current status, interests, and developments in assessing patient-specific dosimetry, which will define the future of this particular treatment modality. In addition, we will discuss the challenges and opportunities of the existing dosimetry standards to measure and calculate the radiation dose delivered to patients, which is essential for ensuring treatments’ safety and efficacy. Finally, this article intends to provide an overview of the current state of 177Lu- tagged radioligand therapy and highlight the areas where further research can improve patient treatment outcomes.